Razvoj kontejnerizacije u pomorstvu svijeta - Ivović, Jovo (Promet - Traffic&Transportation, 2012)
Some thirty years passed since the commencement of a more vigorous development of modern container vessels. Up to this point of time we have had operating four generations of container vessels while the fifth, still more modern one is in the process of preliminary designing activities. In the period of 1970-1989 liner (general) cargo that lends to containerization reported a 300% increase (ba three times}, the capacities of container vessel fleet by 16, and container transport by 12 so that the share of containerized cargo in the overall general cargo operations increased from 17,5% in 1970 to 77,4% in 1989. In the year 1989 there were 4,300 container vessečs of 2 909 00 teu capacity. The development of port/sea container capacities has been followed by the development of containerization in shipping. In the past decade port container traffic has been developing at the average annual rate of 15,9% and then until the year 1984 at 4,2% to reach over the past two years the figure of 8% annual growth. The existing annual container port traffic in sea ports of the worlds is 76 million teu while in the year 200 it is planned to reach the average annual growth of 4,2% to be in the order of 115 milion teu. The development of mainland container bridges makes a positive factor of total development of containerization in transcontinental relations.